Cloning, expression, purification, crystallization and initial crystallographic analysis of FleN from Pseudomonas aeruginosa. Issue 2 (22nd February 2016) - Harshita,; Chanchal,; Jain, Deepti
Abstract : FleN from P. aeruginosa has been cloned, purified and crystallized. Abstract : The assembly of bacterial flagella requires the coordinated expression of a large number of genes in a hierarchical manner. These genes code for structural components of flagella, regulatory components and components that are required for chemotaxis. Stringent spatial and numerical control of flagella biosynthesis is essential for promoting motility and pathogenesis in bacteria. These genes are regulated at the level of transcription. FleN, a P‐loop‐containing ATPase, plays an important role in maintaining flagellar number in Pseudomonas aeruginosa . FleN exhibits anti‐activator activity against FleQ, the global transcriptional regulator of flagellar genes. In order to gain insights into the regulatory mechanism of flagella synthesis, full‐length FleN was crystallized in complex with the nonhydrolyzable ATP analogue β, γ‐imidoadenosine 5′‐triphosphate (AMPPNP) in space group C 2221, with unit‐cell parameters a = 49.1, b = 206.9, c = 103.3 Å. The Matthews coefficient is 2.19 Å 3  Da −1 assuming the presence of two molecules in the asymmetric unit, and the corresponding solvent content is 43.7%. X‐ray diffraction data were collected to a minimum Bragg spacing of 2.21 Å and crystals of FleN–AMPPNP were prepared with selenomethionine‐labelled FleN for ab initio phasing.